The Investigation Process of Prospective Children in Criminal Action - Ari Yudistira; Widayati Widayati (Jurnal Daulat Hukum, 2021)
The objectives of this research are: To identify and analyze the process of investigating child suspects in drug crimes. To find out and analyze the obstacles in the process of investigating child suspects in drug crimes and their solutions. This study uses a sociological juridical approach, with descriptive analytical research specifications. The data used in this research is secondary data obtained through library research and primary data. The results of this study on process of investigating child suspects in drug crime includes: a) Detention period for children is only valid for a maximum of 7 (seven) days and can be extended by the public prosecutor for a maximum of 8 (eight) days. b) Investigations against perpetrators of child crime are carried out by child investigators. c) In conducting an investigation, the investigator is obliged to ask for consideration from the Correctional Center (BAPAS). Barriers: a) The duration of research from the Correctional Institution (BAPAS). b) The unavailability of special investigators for children due to limited Human Resources (HR). The solution: a) To increase the ability of investigators to carry out investigations so that they are able to resolve cases during the period of time the child is detained according to the rules, namely 7 (days) of work and can extend detention by 8 (eight) working days b) Increasing the working relationship with BAPAS so that research and research results on children can be completed immediately. So that the results of the research can be completed immediately before the investigator hands over the child and evidence to the Public Prosecutor (JPU).